Nutrient recycle from defatted microalgae (Aurantiochytrium) with hydrothermal treatment for microalgae cultivation. (March 2017) - Aida, Taku Michael; Maruta, Ryouma; Tanabe, Yuuhiko; Oshima, Minori; Nonaka, Toshiyuki; Kujiraoka, Hiroki; Kumagai, Yasuaki; Ota, Masaki; Suzuki, Iwane; Watanabe, Makoto M.; Inomata, Hiroshi; Smith, Richard L.
Graphical abstract: Highlights: Nutrient recycle from defatted microalgae for microalgae cultivation is evaluated. N and P can be recovered from defatted microalgae by hydrothermal treatment. Nutrient efficiency depends on reaction conditions of the hydrothermal treatment. Hydrothermal treatment at high temperature conditions produce anti-growth agents. Abstract: Defatted heterotrophic microalgae ( Aurantiochytrium limacinum SR21) was treated with high temperature water (175–350 °C, 10–90 min) to obtain nitrogen and phosphorous nutrients as a water soluble fraction (WS). Yields of nitrogen and phosphorous recovered in WS varied from 38 to 100% and from 57 to 99%, respectively. Maximum yields of nitrogen containing compounds in WS were proteins (43%), amino acids (12%) and ammonia (60%) at treatment temperatures of 175, 250 and 350 °C, respectively. Maximum yield of phosphorous in WS was 99% at a treatment temperature of 250 °C. Cultivation experiments of microalgae ( A. limacinum SR21) using WS obtained at 200 and 250 °C showed positive growth. Water soluble fractions from hydrothermal treatment of defatted microalgae are effective nitrogen and phosphorous nutrient sources for microalgae cultivation.